The Impact of Nursing Protocols on Continuous Special Observation. (January 2017) - Ray, Richard; Perkins, Evelyn; Roberts, Patricia; Fuller, Lisa
BACKGROUND: Continuous Special Observation (CSO) is commonly ordered for patients at risk to injure themselves or others and involves assigning staff to monitor one patient at all times. CSO is intrusive, costly, and often has deleterious effects on patient care. Two nursing protocols were developed as alternative interventions to CSO. The first protocol, Psychiatric Nursing Availability (PNA), was designed to treat patients having suicidal or self-injurious thoughts. The second protocol, Psychiatric Monitoring and Intervention (PMI), was designed to prevent violent and impulsive behavior. These protocols had their genesis in a model that encourages nursing autonomous decision making.OBJECTIVE: Identify the impact PNA and PMI had on the number of CSO and their duration.STUDY DESIGN: Nine-year descriptive retrospective analysis of CSO, PNA, and PMI. The data were collected from the unit 15-minute rounding sheets. Descriptive analyses were performed. Interrupted time series analysis was used to determine how the protocols affected frequency and duration of CSO.RESULTS: PNA did not significantly affect CSO; however, PMI did affect its use. There was a downward trend in the number of CSOs after PMI was implemented by 0.07 episodes per month ( p = .0111). The median duration of CSO dropped from 66 hours to 33 hours after PMI was implemented ( p = .0004).CONCLUSION: PMI had the greatest impact on CSO. PMI had a secondary effect of increasing staff availability on the unit that affected CSO's use. The model of nursing care may have influenced this reduction in CSO.